(untitled) (Sciences & Technologie. C, Biotechnologies, 2009)
A set of eight durum wheat genotypes was usedto evaluate the relationship between carbon isotope discrimination (∆.) and grain yield under different rainfall regimes during the 2002-03 and 2003-04 seasons. The study included two old Algeriancultivars (Polonicum, Oued Zenati) and six advanced lines from the CIMMYT / ICARDA durum wheat breeding program. The same set of genotypes was used in 2004-05 and 2005-06 to evaluate the influence ofinter-annual climatic variation. These cultivars represent a wide range of agronomic characteristics. The ∆values allowed the selection of three parents to analyze the genetics of grain-∆: Waha and Mexicali (high-∆) and Oued Zenati (low-∆). In 2003-04, two crosses weremade, Mexicali / Waha (high-∆/ high-∆) and Oued Zenati / Mexicali (low-∆/ high-∆). The parental cultivars and the F2and F3 populations were then grown in 2004-05 and 2005-06 seasons. For the 2006-07 season, three categories of plants were chosen and sown from the F4 population based on their similar heading date and plant height. Estimates of realized heritability were obtained, and the degree of correlation between ∆and grain yield was estimated. At the same time, two field experiments were carried out at Ain Abessa located in the north of the high plateau, and at Beni Fouda located in the east.